NILAI FILOSOFIS TAHFIDZ AL-QUR’AN DALAM MEMBANGUN KECERDASAN SPIRITUAL PESERTA DIDIK SDIT UTSMAN BIN AFFAN SURABAYA - Mus taqim; Uji Nur Hidayati; Salsabila Aisya Alifiyah (Universitas Uluwiyah Mojokerto, 2026)
The development of modern education requires a balance between intellectual competence and spiritual intelligence. In Islamic educational institutions, the tahfidz Al-Qur’an program is not only intended to improve memorization skills but also to internalize Islamic values in students’ daily lives. This study aims to analyze the philosophical values of tahfidz Al-Qur’an in developing the spiritual intelligence of students at SDIT Utsman Bin Affan Surabaya. The study employs a qualitative descriptive approach through observations, interviews, and documentation related to the implementation of the tahfidz program. The findings indicate that tahfidz Al-Qur’an contains philosophical values that contribute significantly to spiritual development, including discipline, patience, sincerity, responsibility, self-control, and closeness to Allah. The process of memorizing and reviewing the Qur’an encourages students to develop awareness of worship, moral sensitivity, and positive social behavior. The tahfidz program also serves as a medium for character building through the internalization of Qur’anic values. The study concludes that tahfidz Al-Qur’an is not merely a memorization activity but an educational process that integrates cognitive, affective, and spiritual dimensions. Therefore, the philosophical values embedded in tahfidz play an important role in shaping students into individuals with strong spiritual intelligence and noble character.